2022
DOI: 10.1177/03000605221098179
|View full text |Cite
|
Sign up to set email alerts
|

Fatal gastrointestinal bleeding associated with acute pancreatitis as a complication of Covid-19: a case report

Abstract: Clinical manifestations of Covid-19 vary widely among patients. Recent studies suggest that up to 15% of patients with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infections develop gastrointestinal symptoms. The location of virus–host cell receptors angiotensin-converting enzyme 2 and transmembrane serine protease 2 has an important role in the pathophysiology and presentation of disease. They are expressed in the respiratory tract, as well as other organs and tissues including exocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
18

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 29 publications
1
23
0
18
Order By: Relevance
“…Ren et al [ 21 ] reported on their endovascular treatment of 159 patients with visceral artery aneurysms and pseudoaneurysms, with 96.9% of patients successfully treated and a 1.9% mortality rate at 30 days. Similar to our case, Mitrovic et al [ 13 , 14 , 15 ] reported successful endovascular resolution of a posterior inferior pancreaticoduodenal artery pseudoaneurysm using the sandwich technique, in which the pseudoaneurysm inflow and outflow were embolized with coils. Jang et al [ 16 ], on the other hand, embolized the pseudoaneurysm with an N-Butyl-Cyanoacrylate-lipiodol composition.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Ren et al [ 21 ] reported on their endovascular treatment of 159 patients with visceral artery aneurysms and pseudoaneurysms, with 96.9% of patients successfully treated and a 1.9% mortality rate at 30 days. Similar to our case, Mitrovic et al [ 13 , 14 , 15 ] reported successful endovascular resolution of a posterior inferior pancreaticoduodenal artery pseudoaneurysm using the sandwich technique, in which the pseudoaneurysm inflow and outflow were embolized with coils. Jang et al [ 16 ], on the other hand, embolized the pseudoaneurysm with an N-Butyl-Cyanoacrylate-lipiodol composition.…”
supporting
confidence: 85%
“…Arterial aneurysmal dilatation develops as a result of damage to the collagen structure at the arterial wall caused by atherosclerosis or hypertension, and is found with the highest incidence at the level of the abdominal aorta [ 5 , 6 , 7 , 8 , 9 ]. In contrast, arterial pseudoaneurysms are connected with trauma, surgical treatments, or the presence of malignancies, but in the case of the pancreaticoduodenal artery, the main reason is the association with chronic pancreatitis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although it is a rare pathology, it is lethal in the absence of intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that the SARS-CoV-2 virus may cause AP[ 10 , 11 ]. A study conducted in Serbia described that 15%-19% of patients with SARS-CoV-2 infections developed gastrointestinal symptoms[ 12 , 13 ].…”
Section: Etiologies Of Non-covid-19 Related and Covid-19-related Apmentioning
confidence: 99%
“…The location of the virus-host cell receptors angiotensin-converting enzyme 2 and transmembrane serine protease 2 plays an important role in the pathophysiology and presentation of COVID-19. These receptors are expressed in the respiratory tract, as well as other organs and tissues including exocrine and endocrine pancreatic cells[ 12 ]. Additionally, systemic inflammation may cause AP, especially in children.…”
Section: Potential Mechanisms Of Covid-19-related Apmentioning
confidence: 99%